2020
DOI: 10.1051/e3sconf/202021020005
|View full text |Cite
|
Sign up to set email alerts
|

Ambition of young people - representatives of Y and Z generations

Abstract: The article presents the results of a comparative analysis of self-assessment of ambition of students - representatives of Y and Z generations. The aim of the study was to identify the similarities and differences in self-esteem of ambition and the degree of its expression among young people of different generations. A cross-sectional survey of young people's ambition was conducted in 2009 (Gen Y youth) and 2020 (Gen Z youth). The study involved 200 young people aged 18-22: 106 young people of generation Y and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…A number of modern studies in psychology, sociology, economics, and other social sciences are devoted to the study of ambition in the context of human social activity. In our previous study, we found similarities in the ambition of representatives of different generations -X and Y generations [9]. Junyi Chai considers ambition as one of three state variables (ambition, retaliation, aspiration)-the model delivers a new measure of individual well-being under both social and historical contexts [10].…”
Section: Introductionmentioning
confidence: 87%
“…A number of modern studies in psychology, sociology, economics, and other social sciences are devoted to the study of ambition in the context of human social activity. In our previous study, we found similarities in the ambition of representatives of different generations -X and Y generations [9]. Junyi Chai considers ambition as one of three state variables (ambition, retaliation, aspiration)-the model delivers a new measure of individual well-being under both social and historical contexts [10].…”
Section: Introductionmentioning
confidence: 87%
“…The main desire of an ambitious person to gain recognition and become a significant person for other people for achievements [1; 2]. Ambition is a universal quality that does not depend, for example, on a person's gender and age, on their belonging to one generation or another [2], etc.…”
Section: Introductionmentioning
confidence: 99%